Odpowiedź:
a)
10x + 20 = 17x+ 30 - 1x
10x + 20 = 16x + 30
10x - 16x = 30 - 20
- 6x = 10
x= 10 : (-6)
x= - 10/6
x= - 1 i 4/6
x= - 1 i 2/3
spr.
10x + 20 = 17x+ 30 - 1x
L= 10x + 20 = 10 * (-1 i 2/3) + 20 = 10 * (-5/3) + 20 = - 50/3 + 20 =
= - 16 i 2/3 + 20 = 3 i 1/3
P = 17x + 30 - 1x= 16x + 30 = 16 * (- 1 i 2/3) + 30 = 16 * (- 5/3) + 30 =
= - 80/3 + 30 = - 26 i 2/3 + 30 = 3 i 1/3
3 i 1/3 = 3 i 1/3
L = P
b)
3 i 2/9 - 1 i 1/8= (sprowadzam ułamki do wspólnego mianownika --> 72)
= 3 i 16/72 - 1 i 9/72 =
= 2 i 7/72
c)
3/7 : 6/14=
= 3/7 * 14/6 = (skracam ułamki)
= 1/1 * 2/2=
= 2/2=
= 1
Szczegółowe wyjaśnienie: